Seeing is believing: Understanding the experiences and needs of marginalized communities living through successive disasters using photovoice - Laura de la Roche; Carlos G. Fuentes; Ailiya Z. Jafry; Omolola E. Adepoju (PLoS ONE, 2025)
Introduction Reports indicate increasing prevalence rates of successive natural disasters, and the negative impact on existing infrastructures are well documented. However, factors impacting outcomes on both communities and individuals remain unclear. For historically underserved communities, the effects of disasters are exacerbated by pre-existing barriers that make efforts to recovery difficult. Thus, understanding the nuance of their circumstances and experience is crucial to helping build resilience in these communities and inform preparedness and response efforts. Objective Through this study, we sought to qualitatively understand the lived experience of historically underserved communities in the context of natural disasters to support the development and/or adoption of resources. Methods Photovoice was used to guide semi-structured interviews with participants recruited from three communities (Kashmere Gardens, Greater Third Ward, Greater Fifth Ward) in Houston, TX. Reflexive thematic analysis was employed to generate themes accurately depicting participant experiences. Reflexivity, persistent observation, and triangulation were employed to increase trustworthiness in analysis. Results Five key themes emerged from analysis: 1) Acute and long-term damage from natural disasters requires sustained recovery efforts; 2) Gaps and opportunities exist in city, state, and federal support mechanisms; 3) Strengthening and expanding support networks and community resources after extreme weather events is critical; 4) Need to address structural barriers to disaster preparedness and coping; and 5) Recognizing and mitigating the broad mental health impacts of natural disasters. Conclusion The lived experiences of individuals from historically underserved communities in Houston highlight a complex interaction of psychosocial, structural, and cultural factors that influence both community resilience and vulnerability. Understanding this interplay is crucial to informing policy efforts that prioritize resilience building in these communities. Implications from these findings are discussed.